Basic Aspects of Ecological and Economical Industrial Waste Material Usage - Miroslav Svoboda; Jaroslava Ledererova; Petr Sulovsky; Michaela Suchardova (The Minerals, Metals and Materials Society, 2008)
"The thinning resources of natural raw materials necessitate an increased degree of waste material recycling. The building industry offers a range of technologies enabling incorporation of industrial wastes into building materials for construction purposes in an economically acceptable way. Our research is focused on finding the appropriate technologies for specific groups of industrial waste materials (IWM). The studied IWM involve coal combustion residues (CCR), desulphurization products, sludges, metallurgical slags, and various other wastes. Many of them contain increased amounts of toxic elements that can under certain conditions get released. In order to prevent this, each specific IWM requires finding the technology that best ensures the binding of toxic elements in the building matter are fixed for the long term.Introduction The sustainable development of mankind is more than ever viewed as a matter of resources. Many aspects of the switch from a throw-away to a recycling society concern one of the largest consumers of natural resources and producer of greenhouse gases, the building industry. One of the biggest tasks lying before the researchers in the field of building materials is to find substitute or alternative raw materials that would save the thinning reserves of natural resources. The most promising and natural way is to replace the traditional raw materials with rejected and unwanted products of industrial processes, classified as wastes. These of course are not produced with the primary intention of achieving some desired properties. The usage of industrial wastes therefore involves finding the optimal way of usage their existing positive (from the point of view of utilizations) properties and minimizing the impact of their undesired properties, i.e. from the perspective of the considered application."